Inter-referencing Asian Canadian Studies: imagining diasporic possibility outside the (Canadian) nation. Issue 2 (3rd April 2019) - Kim, Christine; Lee, Christopher
ABSTRACT: This paper proposes to use inter-Asian methodologies to reread Asian Canadian Studies. As an intellectual and political project, Asian Canadian Studies has largely been constituted through its responses to the Canadian nation-state and anti-racism alliances but has failed to seriously engage with Asia as a critical problematic. Informed by theories and practices of inter-referencing developed through Inter-Asia critique, we reconsider the specific pressures, local debates, and historical moments that have produced the field's central arguments and reframe the field as a series of localized reference points in dialogue with each other as well as with Asia. We conclude by turning to Madeleine Thien's novel Dogs at the Perimeter in order to ask what it might mean to localize Asian Canadian Studies and reposition it as part of a transpacific rather than nation-based formation.